Diagnostic imaging for suspected pulmonary embolism during pregnancy and postpartum: A comparative radiation dose study. Issue 3 (26th May 2022) - Tester, Jodie; Rees, Megan; Pascoe, Diane; Earl, Victoria; Einsiedel, Paul; Lim, Wen Kwang; Irving, Louis; Hammerschlag, Gary
Abstract: Introduction: To compare the radiation dose exposure and diagnostic efficiency of computed tomographic pulmonary angiography (CTPA) and ventilation/perfusion imaging (V/Q) for clinically suspected pulmonary embolism (PE) in pregnant and postpartum women in a tertiary hospital setting. Methods: A retrospective cohort study of 473 pregnant and postpartum women referred for CTPA or V/Q for clinically suspected PE between January 2013 and December 2018 at a tertiary hospital. Maternal effective radiation dose, breast‐absorbed radiation dose and fetal‐absorbed dose estimates were calculated. Diagnostic yield was evaluated from radiological findings. Results: Computed tomographic pulmonary angiography (CTPA) was more commonly used for the imaging of suspected PE in pregnant and postpartum populations (51.9% vs. 48.1% and 77.1% vs. 22.9%, respectively). CTPA was associated with higher maternal effective and breast‐absorbed doses (maternal effective CTPA 4.7 (±2.9) mSv (millisievert), V/Q 1.7(±0.8) mSv (mean difference 2.93 mSv P  < 0.001), and breast‐absorbed CTPA 8.0 (±5.2) mGy (milligray), V/Q 0.3 (±0.1) (mean difference 7.67 mGy P  < 0.001), respectively). Fetal radiation dose exposure was low. The incidence of positive PE was 5.5%. Indeterminate rates of CTPA and V/Q were 3.0% and 5.5% ( P  = 0.176), respectively. Conclusions: Compared to V/Q, CTPA is associated with higher maternal and breast radiation dose; however, modern CT scanners achieve lower radiation doses than historically described. Fetal radiation dose was comparably low. The diagnostic yield of the imaging modalities in pregnant and postpartum women is similar. Revision of guidelines should occur with the advances in CT technology.